Adverse events associated with currently used medical treatments for cystinuria and treatment goals: results from a series of 442 patients in France. (25th March 2019) - Prot‐Bertoye, Caroline; Lebbah, Saïd; Daudon, Michel; Tostivint, Isabelle; Jais, Jean‐Philippe; Lillo‐Le Louët, Agnés; Pontoizeau, Clément; Cochat, Pierre; Bataille, Pierre; Bridoux, Franck; Brignon, Pierre; Choquenet, Christian; et al.
Abstract : Objective: To evaluate medical treatments, in terms of adverse events (AEs) and therapeutic goals, in a large series of patients with cystinuria. Patients and Methods: Data from 442 patients with cystinuria were recorded retrospectively. Crystalluria was studied in 89 patients. A mixed‐effects logistic regression model was used to estimate how urine pH, specific gravity and cysteine‐binding thiols (CBT) correlate with risk of cystine crystalluria. Results: Alkalizing agents and CBT agents were given to 88.8% ( n = 381) and 55.3% ( n = 238) of patients, respectively. Gastrointestinal AEs were reported in 12.3%, 10.4% and 2.6% of patients treated with potassium bicarbonate, potassium citrate and sodium bicarbonate, respectively ( P = 0.008). The percentages of patients who experienced at least one AE with tiopronin (24.6%) and with D‐penicillamine (29.5%) were similar ( P = 0.45). Increasing urine pH and decreasing urine specific gravity significantly reduced the risk of cystine crystalluria, whereas D‐penicillamine and tiopronin treatments did not reduce this risk (odds ratio [OR] 1 for pH ≤6.5; OR 0.52 [95% confidence interval {95% CI} 0.28–0.95] for 7.0 <pH ≤7.5, P  =   0.03; OR 0.26 [95% CI 0.13–0.53] for 7.5 < pH ≤8.0, P <0.001; OR 1 for specific gravity ≤1.005 OR 5.76 [95% CI 1.45–22.85] for 1.006 ≤ specific gravity ≤1.010, P = 0.01; and OR 11.06 [95% CI 2.76–44.26] for 1.011 ≤ specific gravity ≤ 1.014, P < 0.001). Increased urine pH significantly increased the risk of calcium phosphate crystalluria (OR 1 for pH≤ 6.5; OR 6.09 [95% CI 2.15–17.25] for pH >8.0, P <0.001). Conclusion: Adverse events were frequent with D‐penicillamine and tiopronin. Alkaline hyperdiuresis was well tolerated and reduced cystine crystalluria. Urine specific gravity ≤1.005 and urine pH >7.5, while warning about calcium‐phosphate crystallization, should be the goals of medical therapy.